Motivasi belajar mahasiswa rantau dari Luar Jawa: Adakah peran penyesuaian diri? - Inda Wulandari; Suroso; Karolin Rista (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to analyze the relationship between self-adjustment and the learning motivation of overseas students outside Java at the University of 17 August 1945 Surabaya. This type of research uses correlational quantitative research methods. The population in this study were overseas students outside Java, class of 2022, totaling 282 and divided into six faculties. The research sample totaling 165 students was obtained by purposive sampling technique. Data collection used two Likert model scales, namely the learning motivation scale from Chernis and Goleman (2001) with 40 items, and the self-adjustment scale from Schneiders (1964) with 36 items. Data were analyzed using the Product Moment correlation technique. The results of data analysis show that there is a positive and very significant relationship between self-adjustment and student learning motivation, meaning that the higher the self-adjustment, the higher student learning motivation, conversely if self-adjustment is low, student learning motivation is also low. Keywords: Faculty; Gender; Motivation to Learn; Overseas Students; Self Adjusment Abstrak Penelitian ini bertujuan untuk menganalisis hubungan antara penyesuaian diri dengan motivasi belajar mahasiswa rantau luar Jawa di Universitas 17 Agustus 1945 surabaya. Jenis penelitian ini menggunakan metode penelitian kuantitatif korelasional. Populasi pada penelitian adalah mahasiswa rantau luar Jawa angkatan 2022 berjumlah 282 dan terbagi kedalam enam fakultas. Sampel penelitian berjumlah 165 mahasiswa diperoleh dengan teknik purposive sampling. Pengumpulan data menggunakan dua skala model Likert, yaitu skala motivasi belajar dari Chernis dan Goleman (2001) dengan 40 aitem, dan skala penyesuaian diri dari Schneiders (1964) dengan 36 aitem. Data dianalisis dengan menggunakan teknik korelasi Product Moment. Hasil analisis data menunjukkan adanya hubungan yang positif dan sangat signifikan antara penyesuaian diri dengan motivasi belajar mahasiswa, artinya semakin tinggi penyesuaian diri maka semakin tinggi motivasi belajar mahasiswa, sebaliknya apabila penyesuaian diri rendah maka motivasi belajar mahasiswa juga rendah. Kata kunci: Fakultas; Jenis Kelamin; Mahasiswa Rantau; Motivasi Belajar; Penyesuaian Diri